State-Owned Enterprise Restructuring : Better Performance Through the Corporate Structure and Competition - Muir, Russell; Soba, Joseph (World Bank, Washington, DC, 2012)
The legal structure of the modern corporate form has four fundamental elements--separate identity, limited liability for shareholders, centralized management, and transferability of shares. These, together with the dynamics of governance relationship between the owners, the supervisory board, and the executives of the firm, provide internal incentives for efficiency. However, the legal form alone is not sufficient to ensure efficiency. Certain external incentives must be in place for sustainable efficiency gains. Corporate performance is influenced by external pressures from competition in product, factor, debt, and equity markets and by regulation. The interplay of the internal and external incentives causes the managers to act in accordance with the goals of efficiency and profitability set by the owners. Also, it causes the modern corporation to act with a clarity and singleness of purpose. The absence of any of the internal or external incentives can seriously undermine performance.